Numerical assessment of heat transfer and entropy generation of a mixed convection ferrofluid flow under the effect of a non-uniform magnetic field - Kamel Zitouni; Messaouda Boumaaza; Lakhdar Aidaoui; Yahia Lasbet; Houssam Eddin Abdellatif; Shan Ali Khan; Yazid Chetbani; Ahmed Belaadi; Ibrahim M.H. Alshaikh; Djamel Ghernaout (Case Studies in Thermal Engineering)
This study investigated the flow characteristics, entropy generation, and thermal transfer of convection in a vertical and horizontal three-dimensional square duct filled with ferrofluid. The influence of periodic transverse and partial magnetic fields (MFs) along the walls of a duct having a constant flux density on the flow pattern is explored. The analysis is carried out by examining various geometric and physical parameters, i.e., the Grashof number (Gr) (40 ≤ Gr ≤ 4 × 105), the Hartmann number (Ha) ranged from 0 to 50, Reynolds number (Re = 200) and volume fraction of Fe3O4 nanoparticles (Ø = 0.02). The effect of the various factors in the problem on heat transfer presented by Nusselt number (Nu) and the friction coefficient along the entropy generation have been discussed graphically. Findings show that when the magnetic force is applied transversely (γ = π/2, γ = π/4) under both full and partial circumstances, the total entropy generation decreases with rising Ri and Ha. On the other hand, when it is applied longitudinally (γ = 0), it grows. The opposite tendency is noted for the Nusselt number and therefore the heat exchange. Using the horizontal position leads to accelerated heat transfer, while entropy production is reduced.